2006
DOI: 10.1080/02571862.2006.10634770
|View full text |Cite
|
Sign up to set email alerts
|

Associations of yield and yield components among selected durum wheats (Triticum turgidumL.)

Abstract: Associations of seed yield (SY) and important agronomic traits were studied among selected durum wheats (Triti~um turgidum L.) to establish the relationship and pinpoint the best selection criteria. Controlled glasshouse studies were conducted over two years (2002)(2003) using 14 diverse lines. The result from simple correlation anaIY~is. indica~ed that SY had a significant (P<0.01) negative correlation with heading date as well as positive associations with plant height (PH), number of spikelets per spike (SP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Selection on the basis of grain yield alone is usually not eVective and eYcient, whereas selection along with its component characters could be more eYcient and reliable. Consequently, information on the association between yield and yield components and among the component characters themselves can improve the eYciency of selection in plant breeding programs (Muhammad et al 1994;Shimelis 2006). The objectives of this study were to determine combining ability and association of yield and yield components among cross-combinations of seven selected cowpea [V. unguiculata (L.) Walp] parents.…”
Section: Introductionmentioning
confidence: 99%
“…Selection on the basis of grain yield alone is usually not eVective and eYcient, whereas selection along with its component characters could be more eYcient and reliable. Consequently, information on the association between yield and yield components and among the component characters themselves can improve the eYciency of selection in plant breeding programs (Muhammad et al 1994;Shimelis 2006). The objectives of this study were to determine combining ability and association of yield and yield components among cross-combinations of seven selected cowpea [V. unguiculata (L.) Walp] parents.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of bread wheat yielding capacity increment in breeding programs, the investigation of direct and indirect impact of various characteristics on yield is of major importance (MOHAMMADI et al, 2012). SHIMELIS et al (2006) reported that grain weight per spike and number of spikelet per spike had the most direct and positive effect on grain yield. ZECEVIC et al (2004) obtained by path analysis that the spike length through number of spikelet per spike had the highest positive indirect effect on grain weight per plant.…”
Section: Introductionmentioning
confidence: 99%
“…The knowledge of genetic variability for agronomic traits is the key component in selecting rational parents for hybridization breeding [ 9 ]. Plant height, flag leaf area, peduncle length, spike length, spikelet count per spike, spike count per plant and spike weight are the major components of plant yield selection criteria in breeding, which were observed to be significant genotypic variation in many crops [ 10 , 11 ]. These variations might due to the effect of genotype and environment [ 12 ].…”
Section: Introductionmentioning
confidence: 99%